Perilaku Hidup Bersih dan Sehat Saat Adaptasi Kebiasaan Baru di Pesantren - Suryani, Anih Sri (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2021)
The Covid-19 pandemic has caused the learning and various activities ofstudents in Islamic boarding schools to be stopped. The spread of new Covid-19clusters in Islamic boarding schools, as well as problems with the quality of cleanlinessand environmental health in Islamic boarding schools prior to the pandemic, are ofparticular concern when plans for adopting new habits and Face-to-face Learningwill be carried out in Islamic boarding schools. The research aims to find out how thecondition of knowledge, attitudes, and clean and healthy living behavior of students inIslamic boarding schools; how the influence of knowledge and attitudes of studentson the behavior of clean and healthy life of students; and how clean and healthy livingbehavior is implemented in adopting new habits in Islamic boarding schools. Theresearch was conducted at Islamic Boarding Schools X and Y in Tasikmalaya with amixed-method, namely using quantitative methods with questionnaires and alsoqualitative methods with interviews and literature studies. The results showed that theknowledge index of attitudes and behavior of students was 79.54 (good), the resultsof the correlation test showed that there was a relationship between knowledgeand attitudes and behavior of students related to clean and healthy living behavior.Adaptation of new habits in Islamic boarding schools can be done by paying attentionto internal factors from students in the form of understanding the Covid-19 pandemic,the availability of health facilities and facilities, as well as support factors from boardingschool caregivers and parents. AbstrakPandemi Covid-19 telah menyebabkan pembelajaran dan berbagai aktivitassantri di pesantren dihentikan. Adanya penyebaran klaster baru Covid-19 di pesantrendan juga permasalahan kualitas kebersihan dan kesehatan lingkungan di pesantrensebelum adanya pandemi menjadi perhatian khusus saat rencana adaptasi kebiasaanbaru dan pembelajaran tatap muka akan dilakukan di pesantren. Penelitian bertujuanuntuk mengetahui bagaimana kondisi pengetahuan, sikap, dan perilaku hidup bersihdan sehat (PHBS) santri di pesantren, bagaimana pengaruh pengetahuan dan sikapsantri terhadap PHBS santri, dan diimplementasikan dalam adaptasi kebiasaan barudi pesantren. Penelitian dilakukan di Pesantren X dan Y di Tasikmalaya dengan mixedmethod, yaitu menggunakan metode kuantitatif dengan perangkat kuesioner dan juga kualitatif dengan wawancara dan studi pustaka. Hasil penelitian menunjukkan bahwa indeks pengetahuan, sikap, dan perilaku santri sebesar 79,54 (baik), hasil uji korelasi menunjukkan adanya hubungan antara pengetahuan dan sikap dengan perilaku santri terkait PHBS. Adaptasi kebiasaan baru di pesantren dapat dilakukan dengan memperhatikan faktor internal dari santri berupa pemahaman akan pandemi Covid-19, faktor ketersediaan fasilitas dan sarana kesehatan, serta faktor dukungan dari pengasuh pondok dan orangtua.